THE APPLICATION OF CHORAL AND REPEATED READING STRATEGY TO IMPROVE READING COMPREHENSION OF THE EIGHTH GRADE STUDENTS AT SMP NEGERI 20 SIGI - Pratiwi, Pratiwi; Suriaman, Aminah; Maf’ulah, Maf’ulah; Darmawan, Darmawan (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
This study aimed to evaluate the effectiveness of choral and repeated reading strategies in improving the reading comprehension of eighth-grade students at SMP Negeri 20 Sigi. Using a quasi-experimental design, 46 students were selected through cluster random sampling and divided into experimental and control groups. Data were collected through multiple-choice and essay tests administered before and after the intervention. The experimental group’s mean pretest score was 45.96, increasing to 81.35 post-test, while the control group’s mean rose from 50.30 to 76.04. Statistical analysis showed significant improvement, supported by a two-tailed significance value of 0.000 and a correlation coefficient of 0.696. These findings confirm that choral and repeated reading strategies positively impact students' reading comprehension.